FSMP-19. SEX DIFFERENCES IN REDOX REGULATION UNDERLIE GLUTAMINE DEPENDENCY IN MALE GLIOBLASTOMA. (25th March 2021) - Sponagel, Jasmin; Zhang, Shanshan; Frankfater, Cheryl; Jones, Jill; Selmanovic, Din; Chinnaiyan, Prakash; Rubin, Joshua B; Ippolito, Joseph E
Abstract: Glioblastoma (GBM) is the most aggressive primary brain tumor in adults. GBM occurs more commonly in males but female patients survive significantly longer. Understanding the molecular mechanisms underlying this clinical sex disparity could support novel treatment strategies to improve outcomes for GBM patients. In this regard, we found that male and female GBM patient tissues differ in their metabolite profiles and that male GBM exhibit a higher abundance of amino acid metabolites. We confirmed these findings in a murine model of GBM. Furthermore, we found that male GBM cells are more sensitive to amino acid deprivation. This male-specific dependency on amino acids is almost entirely driven by amino acids involved in reactive oxygen species (ROS) regulation and glutathione synthesis. We found that male GBM cells are more sensitive to depletion of glutathione, which resulted in a significant increase in ROS and cell death in male GBM cells. Moreover, assays of glutathione oxidation demonstrated that male GBM cells exist in a chronically oxidized state. GLS1 mediates the conversion from glutamine to glutamate, a crucial component of glutathione. We found that male GBM cells are more sensitive to GLS1 inhibition with the clinical inhibitor CB-839. This correlated with significantly increased ROS and glutathione levels as well as significantly decreased TCA cycle metabolites in male GBM. Lastly, we found that the TCA cycle metabolite α-ketoglutarate rescues the effects of CB-839 in male GBM cells. Together, these data suggest that (1) male and female GBM differ in their amino acid requirements, (2) male GBM are more dependent on glutathione to regulate ROS levels, and (3) male GBM increase glutathione synthesis at the expense of TCA cycle metabolites upon GLS1 inhibition, suggesting an increased susceptibility to drugs targeting the glutamate/glutathione axis in male GBM. Our data underline the importance of considering sex in metabolic targeting approaches.